Compost as an eco-friendly alternative to mitigate salt-induced effects on growth, nutritional, physiological and biochemical responses of date palm - Mohamed Ait-El-Mokhtar; Abdessamad Fakhech; Raja Ben-Laouane; Mohamed Anli; Abderrahim Boutasknit; Youssef Ait-Rahou; Said Wahbi; Abdelilah Meddich (International Journal of Recycling of Organic Waste in Agriculture)
Purpose In this study, the role of compost application in alleviating salt stress effects on date palm seedlings growth and development was investigated.Method The experiment was set in a randomized design, with or without green waste-based compost, and under two salinity levels (0 and 240 mM NaCl). Growth, mineral uptake, photosynthetic pigments content, oxidative stress markers' accumulation and antioxidant activity were assessed.Results Plants grown under saline condition showed low values of growth attributes while the application of compost increased these attributes under 240 mM NaCl. Salinity increased sodium (Na+) and chlorine (Cl-) ions concentration in plants and reduced phosphorus (P), nitrogen (N), potassium (K+) and calcium (Ca2+) uptake. The presence of compost mitigated these effects by improving the concentrations of the essential elements (P, K+, N and Ca2+) in both plant shoots and roots and by limiting salt ion (Na+ and Cl-) toxicity and thereby induced higher K/Na and Ca/Na ratios. Furthermore, leaf water status, stomatal conductance and photosynthetic efficiency were increased and were coupled with high chlorophyll and protein concentrations in plants amended with compost under salt stress. NaCl stress induced high lipid peroxidation and H2O2 accumulation; however, the application of compost lowered these two parameters in stressed plants through stimulation of the antioxidant enzymes activity and increasing soluble sugars and proline accumulation.Conclusion Results suggest that the green waste-based compost can boost date palm seedlings tolerance in salt-affected soils by mitigating the different adverse effects of salinity stress.